PENYUSUNAN PROSEDUR UNTUK PRAKIRAAN BEBAN PERAWATAN NON-RUTIN DI MRO XYZ (STUDI KASUS: C-CHECK BOEING 737NG) - Graciova, Dave
Maintenance, Repair, and Overhaul (MRO) need a high percentage of on-time Turnaround Time (TAT). In 2019, there is a 29% difference between the plan and the actual TAT in MRO XYZ. Based on the observation, there is no planning to do non-routine maintenance. 54% of the total maintenance is the non-routine maintenance, therefore non-routine maintenance needs to be planned. This will be the main focus of this final project. The first step is to analyze the routine maintenance that dominates the non-routine maintenance based on ATA Chapter and MPD Number using Pareto Analysis. And then, determine and develop a procedure and variables that will be used to forecast the Non-Routine Ratio (NRR). The last step is to implement the procedure to get the NRR forecast model and also as a part to test the forecasting procedure. Non-routine maintenance tasks are dominated by several routine maintenance tasks, that can be divided by ATA Chapter, MPD Number, and task category. Based on ATA Chapter 53, 25 and 57. Based on MPD number 53-140-00, 53-800-00 and 53-866-00. Based on task category is DVI for system, internal GVI for structure, and external inspection for zonal. The load forecasting procedure for B737NG C-Check NRR is composed of C-Check number, aircraft’s age, the ratio of ATA 53, the ratio of ATA 25, and the ratio of ATA 57. The NRR forecast model can be developed to give more accurate results by the addition of some variables, for example, Flight Hours (FH) and Flight Cycles (FC).